2005
DOI: 10.1242/jcs.02324
|View full text |Cite
|
Sign up to set email alerts
|

The lipid composition of autophagic vacuoles regulates expression of multilamellar bodies

Abstract: Multilamellar bodies (MLBs) are responsible for surfactant secretion in type II alveolar cells but also accumulate in other cell types under pathological conditions, including cancer and lysosomal storage diseases such as Niemann-Pick C (NPC), a congenital disease where defective cholesterol transport leads to its accumulation in lysosomes. Mv1Lu type II alveolar cells transfected with Golgi β1,6 N-acetylglucosaminyltransferase V (Mgat5), enhancing the polylactosamine content of complex-type N-glycans, exhibit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
72
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(78 citation statements)
references
References 86 publications
3
72
0
Order By: Relevance
“…Our TEM study showed that in them SMCs within the tunica media lost their concise arrangement and possessed intracellular structures typical for abnormal lipid accumulation [20]. Such structures were found previously in SMCs in the ductus arteriosus just before its physiological closure [21].…”
Section: Discussionsupporting
confidence: 66%
“…Our TEM study showed that in them SMCs within the tunica media lost their concise arrangement and possessed intracellular structures typical for abnormal lipid accumulation [20]. Such structures were found previously in SMCs in the ductus arteriosus just before its physiological closure [21].…”
Section: Discussionsupporting
confidence: 66%
“…A couple of recent reports indicated that endogenous lipid flux was involved in autophagy. 32,33 Here we showed that exogenously introduced cationic lipids were effective enhancers of autophagy. To our knowledge, it is the first report demonstrating that autophagy is involved in transfection mediated by cationic lipids.…”
Section: Discussionmentioning
confidence: 98%
“…Potential involvement of mitochondria autophagy is further supported by the observation of abundant multilamellar bodies adjacent to the cytosolic vesicles (Figure 2E); these bodies have been reported to be late lysosomal organelles or autolysosomes generated by active autophagic flux 17…”
Section: Resultsmentioning
confidence: 65%